Structured COBOL programming - Shelly, Gary B.; Cashman, Thomas J.; Foreman, Roy O. (Danvers, Mass. : International Thomson pub., 1996)
Introduction to Cobol and program development; A complete Cobol program; Environment and data divisions; IF, MOVE, and data validation; Arithmetic statements and branching; The Cobol Sort statement and record selection processing; Tables, table processing, and control breaks; Data manipulation and sequential file maintenance; Indexed and relative files; The report writer feature and declaratives.
Keywords: Computers; COBOL (Computer program language); Structured programming